Management of effluent discharges: A dynamic modelling game - Krawczyk, J.B (School of Management Working Papers, 1994)
This paper is concerned with the problem of the management of effluent dumped into a stream by identifiable polluters. The problem involves a Regional Council which imposes environmental levies on the polluters whose economic activity, other-wise beneficial for the region, results in pollution of the stream. The model for the problem of effluent management is formulated as a dynamic game between the Re-gional Council and the polluters. The game is "played" in discrete time. The players in the game are the polluters ("followers") and the Council (the "leader"). This for-mulation leads naturally to a Stackelberg concept of solution for the game at hand. Because of the obvious difficulties implied by this solution concept, an equilibrium will be sought through the use of an applicable Decision Support Tool wherever an analytical solution appears intractable. The polluters are supposed to be myopic and small; and the Regional Council is interested in promoting production, collecting taxes, and in the clean environment. The model of spread of the pollution within the stream allows for advection and biodegradation.